Development of Digital Pocket Book Media Based on Augmented Reality on the Material of Molecular Geometry Forms - Sri Adelila Sari; Hamelia Putri; Corrienna Abdul Talib (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2025)
This research aimed to develop Augmented Reality (AR)-based digital pocket book media on molecular geometry form materials and measure student feasibility, as well as students’ motivation, and learning outcomes. The study employed an R&D method using a 4D model (Define, Design, Develop, Disseminate). The research instruments include validation sheets, motivation questionnaires, learning outcome tests, and teacher response questionnaires. The validation results indicated that the media was highly feasible, with feasibility scores of 90.43% and 95.83% of media experts. Students’ learning motivation increased, with an average score of 86.66% (high category). Student learning outcomes also improved significantly with an N-Gain value of 0.81 (high category). Teachers' response to the media reached 96.5% (very high category). These results showed that the AR-based digital pocket book media was effectively used in chemistry learning, particularly ini visualizing abstract molecular geometries and enhancing student motivation and learning outcomes.